Artemether-Soluplus Hot-Melt Extrudate Solid Dispersion Systems for Solubility and Dissolution Rate Enhancement with Amorphous State Characteristics. (4th April 2013) - Fule, Ritesh A.; Meer, Tarique S.; Sav, Ajay R.; Amin, Purnima D.
Abstract : This work studied artemether (ARTM) solid dispersion (SD) formulation using mixture of polymer excipient Soluplus, PEG 400, Lutrol F127, and Lutrol F68 melts at temperatures lower than the melting point of ARTM using a laboratory-size, single-screw rotating batch extruder. The effects of three surfactants PEG 400, Lutrol F127, and Lutrol F68 and parameters like mixing temperature, screw rotating speed, and residence time were systematically studied. SEM, XRD, and FT-IR were employed to investigate the evolution of ARTM's dissolution into the molten excipient. Differential scanning calorimetry (DSC) was used to quantitatively study the melting enthalpy evolution of the drug. The results showed that the dissolution rate increased with increasing the ratio of polymer and surfactant to that of drug. It was concluded that the dissolution of the drug in the polymer melt is a convective diffusion process and that laminar distributive mixing can significantly enhance the dissolution rate. The aqueous solubility and dissolution rate of prepared solid dispersion were significantly enhanced. In vitro antimalarial studies revealed marked improvement in IC50 values. Thus hot-melt extrusion (HME) is a promising technology for improving solubility and dissolution profile of ARTM.